دور قادة المسلمين في تعزيز الإبداع في مجتمعاتهم (The Role of Muslim Leaders in Promoting Creativity in their Communities) - بادي جمال أحمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص تناقش هذه الورقة مفهوم الإبداع من المنظور الإسلامي، وتبيّن أوجه اهتمام قادة المسلمين به وتعزيزهم له في مجتمعاتهم بدءا بنبينا صلى الله عليه وسلم وخلفائه الراشدين رضي الله عنهم وغيرهم. وتحاول الإجابة عن بعض الأسئلة أهمها: كيف أسهم قادة المسلمين في تعزيز الإبداع في مجتمعاتهم على المستويات العلمية والسياسية والاقتصادية؟ وما دور البيئة المشجعة على الإبداع التي أوجدوها في تحفيز علماء المسلمين على الاختراع؟ وما أثر تلك الاسهامات في رقي مجتمعاتهم خاصة، وبقية المجتمعات والحضارات الأخرى على وجه العموم؟ الكلمات المفتاحيّة: إسلام، إبداع، علم، قادة، إسهامات. Abstract This paper discusses the concept of creativity from an Islamic perspective, and it shows the interest of Muslim leaders in creativity and its enhancement in their communities, starting with our Prophet (s.a.w.), the righteous caliphs, and others. The paper attempts to answer some fundamental questions, mainly: How did the Muslim leaders contribute to promoting creativity in their societies at the scientific, political and economic levels? And what was the role of prompting environment on the creativity that motivated Muslim scientists to invention? What was the impact of those contributions on the advancement of their societies in particular, and other societies and civilizations in general? Keywords: Islam, Creativity, science, leaders, contributions, inventions.